Jogos de realidade virtual como ferramentas coadjuvantes em tratamentos para o desenvolvimento integral de indivíduos diagnosticados com transtorno do espectro autista - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The aim of this study is to point out the possibilities of using electronic virtual reality games in treatments to improve the integral development of children diagnosed with Autism Spectrum Disorder (ASD). For the construction of this dissertation, the Multipaper format was adopted, which presents a dissertation or thesis as a collection of publishable articles, accompanied or not by an introductory chapter and final considerations. For the first, data was collected using the Web Of Science, SciElo, PubMed and Scopus databases, resulting in more than 13,000 documents. After selection, the data used was analyzed using the Methodi Ordinatio, which guides the search, selection, collection and classification of scientific articles published in indexed journals. In the second article, data was collected from the Scopus database and the selected studies were analyzed bibliometrically using the Bibliometrix package from RStudio, which allows utilities to carry out relevant bibliometric and visual analyses based on an interactive web interface. The third article used a narrative methodology, describing a brief history of video games and then surveying peripherals with clear potential for use in the treatment of children with ASD. Through the studies, it can be concluded that there are clear trends in the use of electronic games and VR as supporting tools in the treatment of individuals diagnosed with ASD, especially with regard to social skills. The increase in research on the subject has boosted the development and improvement of the game designers produced, consequently improving the treatment of these individuals. This scenario reinforces that the use of these technologies tends to grow and gain ground within the multiple treatments made possible for individuals diagnosed with ASD.
Keywords: Transtorno do Espectro Autista; Realidade Virtual; Jogos Eletrônicos; Autism Spectrum Disorder; Virtual Reality; Electronic Games; CNPQ::CIENCIAS SOCIAIS APLICADAS